A linguistically level playing field: English-medium sport officiating between linguistic imperialism and cultural appropriation - Jacob Kornbeck (Karolinum Press, 2016)
This article revisits four problem areas of the use of English as a lingua franca by sports officials (including coaches, referees, etc.) at international sporting events which were recently identified in an editorial by McNamee in the journal Sport, Ethics and Philosophy. These propositions are revisited by drawing on, inter alia, the theoretical models of 'linguistic imperialism' and 'cultural appropriation'. The argument is made, in particular, that the ability of so-called 'non-native' users of English must not be underrated.